Covalent Modification of a Glassy Carbon Surface by Electrochemical Oxidation of 3,3’-Diaminobenzidine - Ender Mulazimoglu, Ibrahim (Asian Journal of Chemistry, 2010)
3,3'-Diaminobenzidine was covalently modified on the glassy carbon electrode surface by electrochemical oxidation. Electrochemical and spectroelectrochemical behaviours of 3,3'-diaminobenzidine were investigated by cyclic voltammetry and electrochemical impedance spectroscopy (EIS). The modification of 3,3'-diaminobenzidine on the glassy carbon electrode was performed in the -500 and +1500 mV potential range with a scan rate of 100 mV s-1 and 10 cycles. The presence of 3,3'-diaminobenzidine at the glassy carbon electrode surface was characterized by cyclic voltammetry and electrochemical impedance spectroscopy. Cyclic voltammetric studies indicate that the process was irreversible and diffusion controlled.